Development of Organizational Mechanisms of Environmental Management of The Economy - Shanazarova Gulyora Bakhtiyarovna (Research Parks Publishers, 2024)
This article examines the development of organizational mechanisms of environmental management in the economy. It discusses the drivers behind this development, including the need for environmental risk mitigation, regulatory compliance, and meeting stakeholder expectations. Various initiatives are explored, such as environmental management systems, sustainable practices, goal setting, audits, and reporting. The benefits of integrating environmental management into operations are outlined, including resource efficiency, cost savings, reputation enhancement, and long-term sustainability. Overall, organizational mechanisms play a critical role in fostering an environmentally responsible economy and promoting sustainable economic development.